Crack-Like Flaws Pressure Vessel Fitness-For-Service Assessments and Software Programming Based on API RP579. (2015) - Zhou, X.J.; Duan, Q.Q.; Zhang, H.; Zhao, L.; Wu, X.Y.
Abstract: Fitness-For-Service (FFS) assessments are quantitative engineering evaluations, which are especially used in oil and gas industry. Crack-like flaws is one of the major failure modes of pressure vessels. The main purpose of this paper is to study the residual strength evaluation of crack-like flaws pressure vessels. Firstly, domestic and foreign FFS assessments about crack-like flaws pressure vessels have been studied in the paper. Secondly, the assessments in API579 have been studied. Then this paper introduced the software of crack-like flaws assessments which is based on BS structure and is completed by Sql server and Visual studio with C# and database. An example has been given to obtain a software result, which is compared with a handed result in order to verify the accuracy of software.